Efek Pupuk Kascing Dan Klon Terhadap Pertumbuhan Bibit Tanaman Kakao (Theobroma Cacao L.) - Angela Marice Dua Pare; Sunar Wahid; M. Husni (Fakultas Pertanian Universitas Borobudur, 2023)
This research was carried out at the Experimental Garden of the Faculty of Agriculture, Borobudur University. This research was conducted for 3 months starting from September to November 2022. The purpose of this study was to determine the interaction effect of vermicompost fertilizer on cocoa nurseries. The experimental design used in this study was a randomized block design (RBD). The first factor was 4 doses of vermicompost fertilizer (0g, 75g, 100g, 200g) and the second factor was 2 cocoa clones (MCC1 and SUL1). Each treatment contained 4 sample plants which were repeated 3 times, so that in total there were 120 plant polybags.